Changes in Thickness of Tangential Zone of Ageing Male Human Articular Cartilage of Knee Joint - Shaista Ali , Ifra Saeed , Samia Sarwar (Journal of Rawalpindi Medical College, 2014)
Background: To study the changes in thickness of tangential zone of male human articular cartilage. Methods: In this descriptive study forty samples of articular cartilage of knee joint were collected from unknown male dead bodies of 21-60 years of age,within six hours of death. Samples showing gross abnormality and deformity and signs of trauma or surgery of the knee joints were excluded. The collected samples of articular cartilage were divided in four groups,depending upon the age of the cadaver i.e. Group A: 21 – 30 years, Group B: 31 – 40 years. Group C: 41 – 50 years. Group D: 51 – 60 years. Articular cartilage of femoral condyle of right sided knee joint was selected. Skin was incised by giving a transverse incision extending from medial to lateral epicondyle of femur. It was retracted upwards and downwards and the quadriceps tendon was exposed. Tendon was cut by giving inverted “U” shaped incision starting above the patella and extending downwards to the tibial condyle on either side of ligamentum patellae. The cut tendon was reflected downwards along with patella to expose the articular cartilage of femoral condyle. Knee joint was flexed and 1 cm x 1 cm full thickness chip of articular cartilage was removed from the tibial surface of femoral condyle, 1 cm medial to the medial margin of intercondylar fossa with the chisel. The specimens were immediately placed in 10% neutral buffered formalin for 48 hour, processed for paraffin embedding. Five micrometer thick sections were made on rotary microtome and mounted on clear albumin coated slides. Masson’s Trichrome stain was used for the evaluations of the thickness of tangential zone with the help of micrometer. The mean thickness was noted by taking of three random thicknesses and dividing them by three in each sample. Results: The mean thickness of tangential zone was 111 ± 12.86 μm in group A , 110 ± 10.54 μm in group B, 60.43 ± 25.85 μm in group C and 58.89 ± 19.65 μm in group D . The difference in mean thickness of tangential zone was statistically significant in all study groups (p-value = 0.000). As age advanced diminishing thickness of tangential zone became evident. Conclusion: In ageing articular cartilage the thickness of tangential zone decreases markedly leading to osteoarthritis. Presence of stem cells makes it focus of intense study for preventive measures and treatment trends